Efeitos de interações de curto alcance e tamanho de clusters em sistemas desordenados - Schmidt, Mateus (2015)
The competition between cluster spin glass and ferromagnetism or antiferromagnetism is studied in this work. The model considers clusters of spins with short-range ferromagnetic or antiferromagnetic interactions (J0) and long-range disordered couplings (J) between clusters. The problem is treated by adapting the correlated cluster mean- eld theory. Phase diagrams T=J xJ0=J are obtained for different cluster sizes ns. The results show that the cluster spin-glass phase is found below the freezing temperature Tf for lower intensities of J0/J. The increase of short-range ferromagnetic interaction can favor the cluster spin-glass phase, while the antiferromagnetic one reduces the cluster spin-glass region by decreasing the Tf . However, there are always critical values of J0 where antiferromagnetic or ferromagnetic long-range orders become stable. The results also indicate a strong influence of the cluster size in the competition of magnetic phases. For antiferromagnetic clusters, the increase of ns diminishes Tf reducing the cluster spinglass phase region. In the ferromagnetic case, the increase of ns enhances the cluster spin-glass phase region.